Core Components of Cardiac Rehabilitation Programs: 2024 Update: A Scientific Statement From the American Heart Association and the American Association of Cardiovascular and Pulmonary Rehabilitation - Brown, Todd M; Pack, Quinn R; Aberegg, Ellen; Brewer, LaPrincess C; Ford, Yvonne R; Forman, Daniel E; Gathright, Emily C; Khadanga, Sherrie; Ozemek, Cemal; Thomas, Randal J (Circulation (New York, N.Y.), 2024)
The science of cardiac rehabilitation and the secondary prevention of cardiovascular disease has progressed substantially since the most recent American Heart Association and American Association of Cardiovascular and Pulmonary Rehabilitation update on the core components of cardiac rehabilitation and secondary prevention programs was published in 2007. In addition, the advent of new care models, including virtual and remote delivery of cardiac rehabilitation services, has expanded the ways that cardiac rehabilitation programs can reach patients. In this scientific statement, we update the scientific basis of the core components of patient assessment, nutritional counseling, weight management and body composition, cardiovascular disease and risk factor management, psychosocial management, aerobic exercise training, strength training, and physical activity counseling. In addition, in recognition that high-quality cardiac rehabilitation programs regularly monitor their processes and outcomes and engage in an ongoing process of quality improvement, we introduce a new core component of program quality. High-quality program performance will be essential to improve widely documented low enrollment and adherence rates and reduce health disparities in cardiac rehabilitation access.